Art crossing borders : the internationalisation of the art market in the age of nation states, 1750-1914 - Baetens, Jan Dirk; Lyna, Dries (2019)
"Art Crossing Borders offers a thought-provoking analysis of the internationalisation of the art market during the long nineteenth century. Twelve experts, dealing with a wide variety of geographical, temporal, and commercial contexts, explore how the gradual integration of art markets structurally depended on the simultaneous rise of nationalist modes of thinking, in unexpected and ambiguous ways. By presenting a radically international research perspective Art Crossing Borders offers a crucial contribution to the field of art market studies"–...